The mediating effect of soft TQM on the relationship between lean practices and innovation skills in Lebanese hospitals - Aoun, Malak lbrahim (2015)
The main objective of this research is to study the mediating effect of soft total quality management on the relationship between lean practices and innovation skills among the staff of Lebanese hospitals. Lean practices are essential to eliminate wastes and advance the quality of healthcare services through the standardization and continuous improvement strategies of Total Quality Management (TQM). However, there is a need to sustain the effectiveness of such strategies by developing the innovation skills of employees and placing greater emphasis on the soft side of TQM. Thus, a theoretical framework was developed based on the theory of constraints and the resource based view theory. After identifying the gaps of previous literature, a quantitative methodology was applied by surveying 352 employees from public and private hospitals in Lebanon. Primary data collected by self-administered questionnaires was found to be valid and reliable when analyzed through SPSS and AMOS software. Based on the SEM analysis, six hypotheses were accepted while four were rejected. Lean practices through its two dimensions; lean strategies and standardization have shown a significant and positive influence on innovation skills. However, soft TQM has a non-significant influence on innovation skills. On the other hand, lean practices have a significant and positive influence on soft TQM through standardization but not through lean strategies. As for the mediating effect, it was proven that soft TQM mediates the relationship between lean practices and innovation skills at the level of standardization but not of lean strategies. This study contributes by offering good implications for healthcare practitioners at the Lebanese hospitals and healthcare organizations in general, to invest more efforts in implementing lean tools and soft TQM. Finally, future researches are suggested to extend this study at geographical factors and different methodological procedure